A Mini Review on Treatment of Wastewater with Membrane Technology - Kerkulah, Emmanuel N.; Jin, Guixuan; Huang, Jinlei; Huang, Xinyi; Liu, Yuling; Ran, Chang’e; Peng, Hao (Journal of Basic & Applied Sciences, 2023)
Wastewater treatment is a continuous environmental problem, which troubles human activities. Numerous efforts have been made over the years to develop newly efficient technologies, including traditional filtration, coagulation-flocculation, and biological treatment systems. Among which, membrane technology is proven to be a significant one. Membranes technology is divided into four categories based on pore size. The four types of membrane technology including micro-filtration, ultra-filtration, nano-filtration, and reverse osmosis. This paper focus on the introduction, advantages, disadvantages and protection of these four membrane processes.